Numerical Study of Two-Winged Insect Hovering Flight (Advances in Applied Mathematics and Mechanics, 2018)
The two-winged insect hovering flight is investigated numericallyusing the lattice Boltzmann method (LBM). A virtual model of twoelliptic foils with flapping motion is used to study the aerodynamicperformance of the insect hovering flight with and without theeffect of ground surface. Systematic studies have been carried outby changing some parameters of the wing kinematics, including thestroke amplitude, attack angle, and the Reynolds number for theinsect hovering flight without ground effect, as well as thedistance between the flapping foils and the ground surface when theground effect is considered. The influence of the wing kinematicparameters and the effect of the ground surface on the unsteadyforces and vortical structures are analyzed. The unsteady forcesacting on the flapping foils are verified to be closely associatedwith the time evolution of the vortex structures, foil translationaland rotational accelerations, and interaction between the flappingfoils and the existed vortical flow. Typical unsteady mechanisms oflift production are identified by examining the vortical structuresaround the flapping foils. The results obtained in this studyprovide some physical insight into the understanding of theaerodynamics and flow structures for the insect hovering flight.